OpenFlow-enabled dynamic DMZ for local networks - Wu, Haotian (Kansas State University, 2017)
Cybersecurity is playing a vital role in today's network. We can use security devices, such as a deep packet inspection (DPI) device, to enhance cybersecurity. However, a DPI has a limited amount of inspection capability, which cannot catch up with the ever-increasing volume of network traffic, and that gap is getting even larger. Therefore, inspecting every single packet using DPI is impractical. Our objective is to find a tradeoff between network security and network performance. More explicitly, we aim at maximizing the utilization of security devices, while not decreasing network throughput. We propose two prototypes to address this issue in a demilitarized zone (DMZ) architecture. Our first prototype involves a flow-size based DMZ criterion. In a campus network elephant flows, flows with large data rate, are usually science data and they are mostly safe. Moreover, the majority of the network bandwidth is consumed by elephant flows. Therefore, we propose a DMZ prototype that we inspect elephant flows for a few seconds, and then we allow them to bypass DPI inspection, as long as they are identified as safe flows; and they can be periodically inspected to ensure they remain safe. Our second prototype is a congestion-aware DMZ scheme. Instead of determining whether a flow is safe or not by its size, we treat all flows identically. We measure the data rates of all flows, and use a global optimization algorithm to determine which flows are allowed to safely bypass a DPI. The objective is to maximize DPI utilization. Both prototypes are implemented using OpenFlow in this work, and extensive experiments are performed to test both prototypes' feasibility. The results attest that the two prototypes are effective in ensuring network security while not compromising network performance. A number of tools for SDN network configuring and testing are also developed.
Keywords: OpenFlow; Software-defined Networking; Security; Traffic enginerring; Demilitarized zone; Local area network